2015
DOI: 10.14476/jomp.2015.40.3.124
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of pH Papers in the Measurement of Salivary pH

Abstract: Purpose: Salivary pH is an easily measurable biochemical marker and related to various intraoral and systemic conditions. The aim of this study was to evaluate the reliability of the salivary pH measurement using pH paper. In addition, the normal values of salivary pH using pH paper were compared to those of pH meter to investigate the validity.Methods: Twenty healthy male participants attended this study (mean age, 24.5±1.47 years). Unstimulated saliva and stimulated saliva were collected from each subject tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…19 The use of pH meter as a quantitative measure of saliva buffer capacity, found to be able to reduce the inherited subjective deviation of the colourimetric systems, accordingly, considered as a valid mean in accurate determination of salivary. 20 The results of this study revealed significant increase in dental caries experience of asthmatic children where with the increase in severity of asthma condition, a higher dental caries would be experienced by the asthmatics particularly the primary dentition without significant adverse effect as the children mature. 7 Similar findings were reported by other researchers that children with bronchial asthma found to be at higher risk for increased dental caries.…”
Section: Discussionmentioning
confidence: 67%
“…19 The use of pH meter as a quantitative measure of saliva buffer capacity, found to be able to reduce the inherited subjective deviation of the colourimetric systems, accordingly, considered as a valid mean in accurate determination of salivary. 20 The results of this study revealed significant increase in dental caries experience of asthmatic children where with the increase in severity of asthma condition, a higher dental caries would be experienced by the asthmatics particularly the primary dentition without significant adverse effect as the children mature. 7 Similar findings were reported by other researchers that children with bronchial asthma found to be at higher risk for increased dental caries.…”
Section: Discussionmentioning
confidence: 67%
“…The scores are summed ranging from 11 (no dry mouth) to 55 (extremely dry mouth). Some items refer directly to symptoms related to xerostomia (2,4,8,9,10,11) and others refer to coping strategies (1,3,6) as well as functioning limitations (5, 7) [2].…”
Section: Xerostomia Inventorymentioning
confidence: 99%
“…Unstimulated saliva samples were collected for 5 minutes by spitting method in graded tubes (Fig. 1) [1,8]. Then, salivary glands were stimulated by chewing a paraffin pellet (Aurosan GmbH, Essen, Germany; Fig.…”
Section: Saliva Collectionmentioning
confidence: 99%
See 2 more Smart Citations